2018
DOI: 10.1016/j.ijcard.2018.08.087
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial function is disturbed in a hypertensive diabetic animal model of HFpEF: Moderate continuous vs. high intensity interval training

Abstract: The present study provides evidence that endothelial dysfunction occurs in experimental HFpEF and that ET, independent of the studied training modality, reverses endothelial dysfunction and specific molecular alterations. ET may therefore provide an important therapeutic intervention for HFpEF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
2
22
2
1
Order By: Relevance
“…As previous studies have shown, the ZSF1‐obese animals developed signs of HFpEF [elevated E/e′, elevated left ventricular end‐diastolic pressure (LVEDP), and preserved LVEF] at age of 20 weeks 17–20 . In addition, these animals show exercise intolerance, 20,21 reduced skeletal muscle contractility, 21 and impaired endothelial function 22 …”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…As previous studies have shown, the ZSF1‐obese animals developed signs of HFpEF [elevated E/e′, elevated left ventricular end‐diastolic pressure (LVEDP), and preserved LVEF] at age of 20 weeks 17–20 . In addition, these animals show exercise intolerance, 20,21 reduced skeletal muscle contractility, 21 and impaired endothelial function 22 …”
Section: Introductionmentioning
confidence: 72%
“…Regarding the co‐morbidities triggering HFpEF like obesity, diabetes mellitus, hypertension, and hyperlipidaemia, it is well accepted that they are also associated with an increased risk to develop atherosclerosis/endothelial dysfunction and aortic stenosis (AS) 23,24 . The development of endothelial dysfunction in HFpEF is well accepted, 25,26 and recently, our group reported endothelial dysfunction also in ZSF1‐obese rats 22 . With respect to the association between HFpEF and AS, not much is known so far.…”
Section: Introductionmentioning
confidence: 95%
“…64 Recent evidence from animal models of HF have shown that high-intensity interval training can attenuate endothelial dysfunction in both female and male rats, which seems to act via mechanisms specifically lowering oxidative stress in males and increasing endothelial nitric oxide synthase expression in females. 75,76 Whether these molecular benefits are paralleled in male and female patients with HF remains unclear. Furthermore, sex-specific substrate utilization could play a key role in the exercise response in women and may fill the above-mentioned gap in the literature with regards to the effectiveness of exercise-based CR.…”
Section: Future Targets and Open Questions In Translational Cr Researchmentioning
confidence: 99%
“…75,162,163 More recently this line of research included a more clinically relevant animal model, in the way that HFpEF develops due to the onset of multiple comorbidities that mirror a metabolic syndrome. 76,164166 Another problem with appropriate animal models may be that most models develop over a short time period, whereas in humans several years or decades sometimes pass before a clear phenotype is established.…”
Section: Challenges and Opportunities In Translational Cr Research Mementioning
confidence: 99%
“…19 The limited number of authentic HFpEF animal models poses a major limitation for the investigation of its pathophysiology and potential therapies for HFpEF. Available rodent models of HFpEF, including the ageing accelerate mouse, 20 the Dahl salt-sensitive (DSS) rat, 19,21 the Zucker fatty/spontaneously hypertensive heart failure F1 hybrid (ZSF-1) rat, 22,23 the db/db mouse, 24 and the transverse aortic constriction (TAC) surgery/deoxycorticosterone acetate (TAC/ DOCA) mouse 25 have been described. However, which one is most suitable in terms of comparability with SM alterations in HFpEF patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%